Pengaruh ENSO (El Nio and Southern Oscillation) terhadap transpor massa air laut di Selat Malaka - Muhammad M; Syamsul Rizal; Junaidi M. Affan (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. This research examines the influence of ENSO (El Nio and Southern Oscillation) in the Malacca Strait with the southern oscillation index using the Pacific Ocean in determining the condition of Normal, El Nio and La Nina as the analysis of mass transpor of sea water, sea surface elevation and the density of the sea. The research methods using the Navier-Stokes equations with force generating tides, winds from the National Centers for Environmental Prediction (NCEP) Year 1980- 007, salinity(Levitus and Boyer, 1994a) and temperature (Levitus and Boyer, 1994b). Equations of motion of the sea water were modeled with the model of Hamburg Shelf Ocean Model (HAMSOM). The results show that the transport in northwestern part of the Malacca Strait is lower, but in the southeastern part is stronger compared to that of in Normal and La Nina events. While in Sea Level Elevation at El Nio event is lower compared to that of in Normal and La Nina events. For sea surface density, the density values are 18.5 s/d 20.5 kg/m3 while for the later 30-50 m, the values are 19-21 kg/m3. Sea surface density and density for layer 30-50 m in th southeastern part of Malacca Strait for El Nio events are higher than that of in normal and La Nina event. Key words: Sea level elevation, sea density and Hamsom model